Managing Sustainability of Fennoscandian Forests and Their Use by Law and/or Agreement: For Whom and Which Purpose? - Diana Tuomasjukka; Staffan Berg; Marcus Lindner (Sustainability, 2013)
Sustainability and sustainable behaviour is of crucial importance in the management of Fennoscandian forests and forest-related industries. This paper reviews a number of voluntary instruments, which aim at promoting or assessing sustainability impacts at different levels. The multitude of available instruments brings confusion in practice, where companies, consumers and investors meet legal and different voluntary regulatory and non-regulatory instruments. The practical suitability and covered sustainability dimension for each instrument is reviewed with an analysis of strengths, weaknesses, actors and purposes for assessing different aspects of sustainability. Each of them is compared against the other in an overview about which sustainability dimensions they cover (workplace, human rights, community, market place, environment, economy). Results highlight covered, overlapping and missing aspects for each approach and how they can support or reinforce each other. Special attention is given to current approaches in impact assessment, particularly on their areas of application (companies, NGOs, products, operations, production practices, etc.), and recommendations for supplementing it with sustainability impact assessment.